2014
DOI: 10.1063/1.4903045
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of anisotropy in shape and interactions in charged platelet suspensions

Abstract: Motivated by the intriguing phase behavior of charged colloidal platelets, we investigate the structure and dynamics of charged repulsive disks by means of Monte-Carlo simulations. The electrostatic interactions are taken into account through an effective two-body potential, obtained within the nonlinear Poisson-Boltzmann formalism, which has the form of anisotropic screened Coulomb potential. Recently, we showed that the original intrinsic anisotropy of the electrostatic potential in competition with excluded… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 69 publications
1
16
1
Order By: Relevance
“…Moreover, there have only been a few theoretical studies of the phase diagram of electrically charged plate-like particles reported so far because the electrostatic interaction potential of two charged disks in suspension has only recently been calculated ( 45 ). Based on this potential, numerical simulations were made to draw rich phase diagrams that present the nematic and columnar phases, among others, but not the lamellar one ( 10 , 46 ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, there have only been a few theoretical studies of the phase diagram of electrically charged plate-like particles reported so far because the electrostatic interaction potential of two charged disks in suspension has only recently been calculated ( 45 ). Based on this potential, numerical simulations were made to draw rich phase diagrams that present the nematic and columnar phases, among others, but not the lamellar one ( 10 , 46 ).…”
Section: Resultsmentioning
confidence: 99%
“…The second surprising feature is that the rings are ordered antinematically, that is, the particle vectors preferentially lie in a plane perpendicular to the nematic director, contrary to what is found in most discotic liquid crystals. Evidence of antinematicity was found in some soft-interaction models for clay particles [21] and deformable dendrimers [22]. It is quite surprising to see this type of order emerging in simple systems of nanorings which interact only through steric repulsion without the need to apply an external field [23].…”
Section: Introductionmentioning
confidence: 99%
“…[192][193][194] A full understanding of their rheological behaviour therefore requires a combination of theory, molecular modelling and experimental work. Developments in the theoretical understanding of these systems have suggested a rich interplay between the effects of shape and other properties such as charge, 18,196 enabling complex and potentially useful behaviours to be realised. However, examples of empirical studies in which the dimensions of nanoparticles are systematically varied are rare, possibly because this field has traditionally made use of particles such as clay nanosheets, for which well-controlled syntheses have yet to be developed.…”
Section: [H2] Fluid Behaviourmentioning
confidence: 99%